2021
DOI: 10.1186/s12887-021-02658-4
|View full text |Cite
|
Sign up to set email alerts
|

Updated analysis of pediatric clinical studies registered in ClinicalTrials.gov, 2008–2019

Abstract: Background Since the national clinical trials registry (ClinicalTrials.gov) launched in February 2000, more than 360,000 research studies in the United States and over 200 countries have registered. As the characteristics of pediatric clinical studies keep changing over time and the results-reporting mechanism is under evolving, to know about the relevant updates of data elements and the effect of policies on the quality of reporting results is significant. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Despite the policy of the International Council of Medical Journal Editors (ICMJE), which recommends that all investigators report results ( 38 ), we found that the quality of results reported in the childhood obesity registry is still poor. These conclusions are consistent with Yang et al ( 18 ). In clinical studies of mental health and neurology ( 30 , 39 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Despite the policy of the International Council of Medical Journal Editors (ICMJE), which recommends that all investigators report results ( 38 ), we found that the quality of results reported in the childhood obesity registry is still poor. These conclusions are consistent with Yang et al ( 18 ). In clinical studies of mental health and neurology ( 30 , 39 ).…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have found that pediatric clinical trials are terminated frequently ( 19 , 20 , 26 ). Thousands of children have participated in these trials, which means considerable inefficiency and a waste of financial resources ( 18 ). However, the early termination rate of pediatric obesity trials (4.3%) was lower than that of neonatal clinical trials, pediatric cardiovascular trials, pediatric psychological trials, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…gov and ChiCTR databases involved children in China, and the number of clinical trials for antineoplastic agents ( n = 254, 18.3%), anti-infectives ( n = 156, 11.2%) and vaccines ( n = 154, 11.1%) was the largest, it showed that distribution of the indications of the research drugs was quite different between drug registration trials and non- registration trials. Another research based on the ClinicalTrials.gov database showed nearly 53,000 trials related to children were registered from January 2008 to December 2019, indicating less than 14.7% of the registered trials involved children all over the word [ 20 ].…”
Section: Discussionmentioning
confidence: 99%